Obtusifolin ameliorates dry eye model in rats by reducing inflammation and blocking MAPK/NF-κB pathways - Dan Zhu; Xiao-Yang Wu; Liang-Chang Li (International Journal of Ophthalmology)
AIM: To investigate the functions and potential mechanisms of obtusifolin in dry eye disease (DED) in a rat model. METHODS: A rat DED model was established via topical administration of benzalkonium chloride (BAC), followed by administration of obtusifolin. Conjunctival irritation score and tear production were measured to evaluate DED symptoms. Enzyme-linked immunosorbent assay (ELISA) was employed for determining inflammatory cytokine levels in rat conjunctiva. Periodic acid-Schiff staining and corneal fluorescein staining were implemented for assessing goblet cell numbers and corneal epithelial defects, respectively. Western blotting showed zonula occludens-1 (ZO-1), matrix metalloproteinase-9 (MMP-9), and mitogen-activated protein kinase (MAPK)/nuclear factor kappa B (NF-κB) signaling-related protein levels in the conjunctiva. RESULTS: Topical application of obtusifolin alleviated conjunctival irritation and enhanced tear production in BAC-induced DED rats. Obtusifolin attenuated conjunctival inflammatory response and goblet cell loss as well as corneal epithelial barrier disruption in DED rats. Obtusifolin suppressed extracellular signal-regulated kinase (ERK), p38, and NF-κB phosphorylation in the conjunctiva of DED rats. CONCLUSION: Obtusifolin ameliorates DED in rats possibly by alleviating inflammation via the inactivation of MAPK/NF-κB signaling.